SOSIALISASI PENYAKIT LAYU PISANG DAN CARA MEMBUAT BIBIT DARI MATA TUNAS DI DESA LEMBONGAN, KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - Suniti, N. W. (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Volume 12 No.1 – April 2013, 2013)
Training to control banana wild disease and to make the healthy banana seed with Persada biopesticide and Biota-L botanical pesticide was held at Lembongam village District of Nusa Penida, Klungkung regency on 28 Juli 2012. Their activities were aimed to improve the farmer knowledge of banana wild disease and made the banana healthy seed and control the banana wild disease. The topics covered were symptom of banana disease, bioecology pathogen, pathogen distribution, control of banana wild disease and made the banana healthy seed with Persada biopesticide and Biota-L botanical pesticide. The training was attended by 31 participants from local farmer of Lembongan village. The methods used in activities were lecture, trainning to make banana healthy seed, application of Persada biopesticide and Biota-l botanical pesticide in field. All farmers were interested in this program because there was the new knowledge for them and they hope this to be continued in the future,